Evaluasi Program Pendidikan Perspektif Model CIPP (Context, Input, Process, Product) - Kurniawati, Esti Wahyu (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study is how to evaluate educational programs is an evaluation that measures educational activities that provide sustainable basic services and involves educational curricula. The evaluation of the CIPP (Contex, Input, Process and Product) model was first initiated by Stufflebeam. Then Sutfflebeam developed the CIPP evaluation model in 1966. Stufflebeam stated that the CIPP evaluation model is a comprehensive framework to direct the implementation of formative evaluation and summative evaluation of program objects, projects, personnel, products, institutions, and systems. The CIPP model looks at four dimensions, namely the context dimension, the input dimension, the process dimension and the product dimension. The uniqueness of this model is that each type of evaluation is related to the decision making tool (decission) concerning the planning and operation of a program. The advantages of the CIPP model provide a comprehensive evaluation format at each evaluation stage.